The Disappearance of Uncanny in Winnie-The-Pooh and its Use for Education - Harahap, Aris Masruri (Universitas Negeri Semarang, 2018)
This article discusses disappearance of uncanny in one of the greatest children novel from The First Golden Age of Children Literature in Britain, Winnie-the-Pooh. The discussion is meant to uncover why the uncanny does not arise when it is read although it has the elements to arise the uncanny. Moreover, the novel is very popular of its canniness. In doing analysis, FreudÃ¢â‚¬Ëœs thoughts on the uncanny help me to find the reason. The analysis resulted that the use of fantasy in the novel and how its story is narrated determine the readers to not concentrate on the uncanny. The disappearance of the uncanny and the emergence of canny in the novel has made the novel as a favorite reading material for children. This, in fact, is an approach to teach children some values which is influenced by the development of children literature since the 18 th century.